A Voice Against Cultural And Moral Degeneration S. Eliot: The Wasteland - Shammi Nagpal (Elementary Education Online, 2023)
T.S. Eliot (1888-1965), an American of New England family was a poet, dramatist and literary critic. The first edition of his Published poems appeared in 1918 but it was The Waste Land (1922) that firmly established his reputation as a poet. He has dealt with a great variety of themes. The early phase of his poetry and the themes are urban and he has depicted the materialistic impact on the soul of the individual. In the later phase of his poetry, his religious bent of mind can be seen more vividly. Eliot was a spokesman of his age. It was an age where religion was losing its hold on the people's minds. It was an age that was changing rapidly as far as moral, religious and cultural values were concerned. People were becoming morally and spiritually impotent and degenerating day by day. It is in The Wasteland where the Eliot has very forcefully expressed the moral and cultural degeneration. The paper is an attempt to study the theme of ‘A voice against moral and cultural degeneration in The Waste Land.